Rapid response manufacturing through a rapidly reconfigurable robotic workcell - Chen, I-Ming (Robotics and computer-integrated manufacturing, 2001)
This article describes the development of a component-based technology robot workcell that can be rapidly configured to perform a specific manufacturing task. The workcell is conceived with standard and inter-operable components including actuator modules, rigid link connectors and tools that can be assembled into robots with arbitrary geometry and degrees of freedom. The reconfigurable “plug-and-play” robot kinematic and dynamic modeling algorithms are developed. These algorithms are the basis for the control and simulation of reconfigurable robots. The concept of robot configuration optimization is introduced for the effective use of the rapidly reconfigurable robots. Control and communications of the workcell components are facilitated by a workcell-wide TCP/IP network and device-level CAN-bus networks. An object-oriented simulation and visualization software for the reconfigurable robot is developed based on Windows NT. Prototypes of the robot workcells configured to perform the light-machining task and the positioning task are constructed and demonstrated.